Review Paper on Multipurpose Agricultural Farming Machine used to enhance the Different Farming Operation for Indian Farmers - Lokhande, P V; Patil, Shrutika Ashok; Mali, A S (International Journal of Engineering and Management Research, 2024)
In India, agriculture provides a living for 70% of the population. However, as the population grows, we see that farms are shared among families; hence, Indian farmers usually owned just two acres of land. Farmers continue to use traditional agricultural practices because they are economically disadvantaged and cannot afford to buy tractors or other costly equipment. Generally, many Indian farmers use he-buffalo, horses, and bullocks for agricultural work. This will not be sufficient to meet the energy demands of the agricultural industry in compared to other countries. This machine is capable of doing four farming operations on a small scale: excavation, seeding, cultivating, and spraying. It will perform that operations using the android app.